Role of Experiential Avoidance and Alexithymia in the Prediction of Psychosomatic Disorder among the Employees at National Iranian South Oil Company - Ali Molaei pardh; Jahangir Karami; Asieh Moradi (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Īlām, 2022)
Introduction: Psychosomatic disorder is one of the most common mental disorders in which meaningful psychological events play an effective role. This study aimed to investigate the role of experiential avoidance and alexithymia in the prediction of psychosomatics disorder among the employees at the national Iranian south oil company. Material & Methods: The statistical population of this descriptive correlational study included all employees at the national Iranian south oil company from 2020 to 2021. The sample size of the present study was obtained at 371 people based on Cochran's formula. Due to the possibility of incomplete questionnaires, 418 employees were selected by the available sampling method. They were then requested to complete the Symptom Checklist-90 (SCL-90), experiential avoidance (AAQ), and alexithymia (FTAS-20). (Ethic code: 140090) Findings: The results of the Pearson correlation coefficient showed a correlation coefficient of 0.39 between experiential avoidance and psychosomatic disorder which was significant at 0.001. Moreover, there was a correlation coefficient of 0.15 between alexithymia and psychosomatic disorder, which was significant at 0.003. In addition, the results of linear regression analysis showed that experiential avoidance could predict psychosomatic disorders. Discussion & Conclusion: Therefore, according to the findings, in order to reduce psychosomatic disorders, it is necessary to conduct interventions on psychological flexibility and emotional expression. Finally, it is suggested that other empirical and quasi-experimental studies be conducted to confirm these results.